Awareness And Knowledge of Mother-To- Child Transmission of HIV/AIDS Among Pregnant Women of Rural Tertiary Care Hospital - Jyoti Dattaramji Bhise; Deepali Deo (National Journal of Community Medicine, 2015)
Introduction: Infected mother to child transmission of HIV/AIDS, in absence of any intervention vary from 20-25%. Awareness of the var- ious aspects of this disease deserves the ultimate importance in pre- venting mother to child transmission of HIV/AIDS. So the study was planned to evaluate awareness and knowledge of mother-to-child transmission of HIV/AIDS and its prevention among pregnant women.